Emotional foundations of the market: Sympathy and self-interest - Bevilacqua, Emiliano (Frontiers in Sociology, 2022)
Sociology shows the role of emotions in economic life. Sympathy and self-interest are crucial individual dispositions to explain the social behavior that shapes market institutions. Adam Smith emphasized the importance that sympathy has in the achievement of stability in social interactions that foster market society. On the other hand, Max Weber argued that disciplined self-interest is essential for the accumulation of capital. Although their analyses differed in some aspects, both Smith and Weber considered emotions to be the key to understanding the moral values that drive economic behavior. This paper will compare Smith's and Weber's theories of the relationship between emotions and the market. Finally, this paper will interpret sympathy and self-interest as the emotional foundations of the market, highlighting the fundamental role that emotions might have in economic analyses.